A corrosion-resistant metal surface composite coating material and preparation method thereof

Through multi-layer doping electrodeposition treatment, the first and second deposited layers are formed on the surface of the stainless steel, which solves the problems of poor stability and low performance of the existing corrosion-resistant coating, and achieves higher corrosion resistance and service life.

CN119615316BActive Publication Date: 2025-04-22SHANXI ARCHITECTURE KEXUE RES YUAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510165952.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-22
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The existing corrosion-resistant coating on the surface of stainless steel has poor stability and low performance in complex environments. The large differences in physical and chemical properties between multi-layer films lead to interlayer cracking, reducing corrosion resistance.

Method used

By adopting multi-layer doping electrodeposition treatment, a first deposit layer and a second deposit layer are formed on the surface of the stainless steel. The first deposit layer improves adhesion, and the second deposit layer consists of a variety of metal ions and polytitanium silicone to improve corrosion resistance.

Benefits of technology

By improving the adhesion of the metal coating to the stainless steel surface and the uniformity of the second deposited layer, a dense metal coating is formed, which significantly improves the corrosion resistance of the stainless steel surface, reduces the penetration of corrosive media, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615316B_ABST
    Figure CN119615316B_ABST
Patent Text Reader

Abstract

The present invention discloses a corrosion-resistant metal surface composite coating material and a preparation method thereof in the technical field of metal plating. A first deposition layer and a second deposition layer are formed on a stainless steel metal surface through a multi-layer doping-type electrodeposition process. The first deposition layer can improve the adhesion between the metal coating and the stainless steel surface and can improve the uniformity of the second deposition layer. The second deposition layer is composed of a variety of metal ions and polytitanium silazane, and can improve the corrosion resistance of the metal coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal plating, and specifically refers to a corrosion-resistant metal surface composite coating material and a preparation method thereof. Background Art

[0002] Stainless steel has good machinability, electrical and thermal conductivity, and is widely used in a variety of technical fields, such as medical equipment, building structure, transportation, ship equipment manufacturing, etc. However, service in corrosive media can easily lead to corrosion failure. In order to extend the service life of stainless steel and improve its corrosion resistance, surface modification is a common and effective method. The preparation of corrosion-resistant coatings on the surface of stainless steel mainly includes vapor deposition, magnetron sputtering, laser processing technology and electrodeposition. Electrodeposition can be used in large-scale production and is suitable for a variety of economical applications, but the electrodeposition adhesion is insufficient and it is easy to peel off under high temperature or high stress environment; magnetron sputtering is often used in the manufacture of decorative coatings, knives, molds, electronic components and optical equipment and other equipment coatings. The metal coating prepared by this method has high hardness and wear resistance, but the coating prepared by this method is often used for decoration and light protection, and has low impact resistance; chemical vapor deposition is a method of depositing a thin film on the surface of stainless steel through a high-temperature chemical reaction, and the coating has strong chemical corrosion resistance and stability. , but the cost of the preparation equipment is high and the energy consumption is high. It is often used for surface modification of high-end parts, such as semiconductors and photovoltaic equipment. The corrosion-resistant coating on the surface of stainless steel includes single-layer corrosion-resistant film, multi-layer corrosion-resistant film and doped composite film. Among them, the single-layer corrosion-resistant film includes a metal film layer and a non-metallic film layer. By covering the surface of the substrate with a metal, ceramic or polymer film layer, the substrate is isolated from the corrosive medium to achieve a protective effect. However, in a complex environment, due to the influence of solid particle flow, erosion and wear, the stability of the single-layer corrosion-resistant film is poor and the performance is low. The multi-layer corrosion-resistant film layer utilizes the synergistic effect of the interlayer structure and performance to enhance the bonding ability between the film layer and the substrate, hinder the diffusion of the corrosive medium, and improve the corrosion resistance. However, the physical and chemical properties of the multi-layer corrosion-resistant film are too different, which is easy to cause interlayer cracking and cause the corrosion resistance to decrease. The doped composite film mainly improves the film structure by doping the second phase particles in the corrosion-resistant film, which can provide better protection for the substrate, but the dispersion of the second phase particles in the film layer is closely related to the corrosion resistance of the composite film, which limits the development of the composite film. Summary of the invention

[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a corrosion-resistant metal surface composite coating material and a preparation method thereof. The present invention provides a corrosion-resistant metal surface coating material and a preparation method thereof. Through multi-layer doping-type electrodeposition treatment, a first deposition layer and a second deposition layer are formed on the stainless steel metal surface. The first deposition layer can improve the adhesion of the metal coating to the stainless steel surface and can improve the uniformity of the second deposition layer; the second deposition layer is composed of a variety of metal ions and polytitanium silazane, which can improve the corrosion resistance of the metal coating.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a corrosion-resistant metal surface composite coating material, which specifically comprises the following steps:

[0005] S1. Pre-grind the stainless steel and nickel plate with a grinder, and then grind the stainless steel surface with 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh sandpaper in sequence, polish until the sample roughness is 2-2.5 μm, wash with deionized water, acetone, and anhydrous ethanol in sequence to obtain pre-treated stainless steel for electrodeposition treatment of cathode, and obtain pre-treated nickel plate for electrodeposition treatment of anode for standby use;

[0006] S2, immersing the pretreated stainless steel and pretreated nickel plate in the degreasing solution, ultrasonically treating them at 400W for 15 minutes, washing them with deionized water, placing them in the activation solution, soaking them for 10-15 seconds, washing them with deionized water and anhydrous ethanol, and setting them aside;

[0007] Preferably, in step S2, the degreasing liquid specifically comprises components of the following concentrations: NaOH 60 g / L, Na2CO3 20 g / L, Na3PO4 50 g / L, Na2SiO3 10 g / L;

[0008] Preferably, in step S2, the activation solution specifically comprises components of the following concentrations: 50 mL / L of concentrated sulfuric acid and 10 mL / L of dilute hydrochloric acid with a mass fraction of 37%;

[0009] S3. Prepare the electroplating solution according to the following mass concentrations: nickel sulfate 100 g / L, sodium chloride 8 g / L, boric acid 30 g / L, sodium sulfate 60 g / L, sodium dodecyl sulfate 0.1 g / L, adjust the pH of the electroplating solution to 5, adjust the electroplating treatment parameters, and the current density is 0.3 A / dm 2 , the electrodeposition temperature is 35°C, the electrodeposition treatment time is 4 minutes, and the first deposition layer is obtained;

[0010] S4. Prepare the electroplating solution according to the following mass concentrations: 4-5 g / L cobalt sulfate, 18-20 g / L nickel sulfate, 150-200 g / L chromium sulfate, 40-50 g / L sodium citrate, 30-35 g / L boric acid, 70-80 g / L potassium chloride, 0.1-0.2 g / L sodium dodecyl sulfate, 0.2-0.4 g / L dopant, adjust the pH of the electroplating solution to 2.5-3, adjust the electroplating parameters, and the current density is 0.15 A / dm 2 , the electrodeposition temperature is 35°C, the electrodeposition time is 30 min, and the second deposition layer is obtained;

[0011] Preferably, in step S4, the method for preparing the dopant specifically comprises the following steps:

[0012] S41, dissolving n-butyl lithium in cyclohexane, adding tetravinylcyclotetrasilazane solution under a dry nitrogen atmosphere, mixing evenly, adding tetramethylethylenediamine, stirring well at 150-200 rpm, reacting for 1-2 hours, filtering, washing the retained solid with n-hexane, and vacuum drying to obtain a tetravinylcyclotetrasilazane lithium compound, which was stored under an argon atmosphere;

[0013] S42, transferring the tetravinylcyclotetrasilazane lithium prepared in step S41 into a toluene-tetrahydrofuran-n-hexane mixed solvent, fully stirring under a nitrogen atmosphere, adding titanium tetrachloride, raising the temperature to 80-100° C., stirring and reacting for 36-48 hours, filtering, removing the solvent in the filtrate, and obtaining polytitanium silazane;

[0014] S43, dissolving the polytitanium silazane prepared in step S42 in tetrahydrofuran, adding 2-mercaptoethanol, mixing evenly, adding benzoin dimethyl ether, stirring at 300 rpm, reacting under ultraviolet light for 5-10 minutes, removing the tetrahydrofuran solvent after the reaction is completed, precipitating with anhydrous methanol, removing unreacted reactants, and vacuum drying to constant weight to obtain a dopant;

[0015] Preferably, in step S41, the mass fraction of n-butyl lithium in cyclohexane is 40-50 g / L;

[0016] Preferably, in step S41, the amount of tetramethylethylenediamine added is 5-10% by volume of cyclohexane;

[0017] Preferably, in step S41, the tetravinylcyclotetrasilazane solution is tetravinylcyclotetrasilazane dissolved in n-hexane, and the mass concentration of the tetravinylcyclotetrasilazane solution is 0.1-0.3 g / mL;

[0018] Preferably, in step S41, the molar ratio between n-butyl lithium and tetravinylcyclotetrasilazane is 4-4.5:1;

[0019] Preferably, in step S42, the mass concentration of the tetravinylcyclotetrasilazane lithium compound in the mixed solvent is 50-60 g / L;

[0020] Preferably, in step S42, the molar ratio between the lithium tetravinylcyclotetrasilazane and titanium tetrachloride is 1:1.2-1.5;

[0021] Preferably, in step S43, the mass concentration of the polytitanium silazane in tetrahydrofuran is 0.1-0.2 g / mL;

[0022] Preferably, in step S43, the mass ratio between the 2-mercaptoethanol and the polytitanium silazane is 1:11-13;

[0023] Preferably, in step S43, the added mass of the benzoin dimethyl ether is 2%-3% of the mass of the polytitanium silazane;

[0024] S5, placing the stainless steel treated in step S4 in a tube furnace, raising the temperature to 700-800°C at 10°C / min under an argon atmosphere, keeping the temperature for 1-2 hours, and then naturally cooling the stainless steel to room temperature in the furnace to obtain a corrosion-resistant metal surface composite coating material;

[0025] The present invention also provides a corrosion-resistant metal surface composite coating material prepared according to the above method.

[0026] The beneficial effects achieved by the present invention are as follows:

[0027] The invention provides a corrosion-resistant metal surface coating material and a preparation method thereof. A first deposition layer and a second deposition layer are formed on a stainless steel metal surface through a multi-layer doping type electrodeposition process. The first deposition layer can improve the adhesion between the metal coating and the stainless steel surface, and can improve the uniformity of the second deposition layer. The second deposition layer is composed of a plurality of metal ions and polytitanium silazane, and can improve the corrosion resistance of the metal coating. In the invention, metal nickel ions are used as the first deposition layer, which can be called a transition layer, and can effectively improve the adhesion between a substrate and a coating. By forming an interactive intermediate layer between the substrate and the final coating, the peeling or shedding of the coating is reduced or prevented. In the invention, multi-metal particles and a dopant are used as the main components of a plating solution and deposited on the first deposition layer. The dopant of the invention is an activated polytitanium silazane. Tetravinylcyclotetrasilazane and metal chloride are used as raw materials. Tetravinylcyclotetrasilazane is reacted with n-butyl lithium. Under the promotion of TMEDA, Li +It can break the NH bond to form N-Li, and then undergo a replacement reaction with titanium tetrachloride to introduce titanium element into the structure of tetravinylcyclotetrasilazane, forming a network structure with tetravalent metal ions as the cross-linking center, thereby increasing the cross-linking density of the polymer, activating it through mercaptoethanol, and hydrophilically activating the vinyl group, thereby increasing its dispersibility in the plating solution. During deposition, the activated polytitanium silazane can interact with metal ions through hydroxyl groups, thereby increasing the deposition of polytitanium silazane and metal ions. Polytitanium silazane can increase the integrity and density of the second deposition layer, thereby preventing the invasion of corrosive media and increasing the corrosion resistance of the metal coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the infrared spectrum of the dopant prepared in Example 1;

[0029] Figure 2 The SEM images of the coating materials prepared in Experimental Example 1 and Comparative Example 1;

[0030] Figure 3 The dynamic polarization curves of the coating materials and bare steel prepared in Example 1 and Comparative Examples 1-3;

[0031] Figure 4 It is a graph showing the anti-corrosion efficiency results of Examples 1-3 and Comparative Examples 1-3.

[0032] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0035] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0036] Example 1

[0037] This embodiment provides a method for preparing a corrosion-resistant metal surface composite coating material, which specifically includes the following steps:

[0038] S1. Take SS316L stainless steel as the anode, with a size of 10×30×1.5mm, take a pure nickel plate with a nickel content of 99.98% and a size of 40×40×3mm, pre-grind the SS316L stainless steel anode plate and the pure nickel cathode plate with a grinder, and then manually grind and polish with 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh SiC sandpaper in sequence, and use a DR300 high-precision roughness tester to test the surface roughness of the SS316L stainless steel anode plate and the pure nickel cathode plate, which are 2.3μm and 2.1μm, respectively. After grinding, use deionized water, acetone and anhydrous ethanol to clean the surfaces of the stainless steel anode plate and the pure nickel cathode plate in sequence to obtain a pretreated stainless steel anode plate and a pretreated pure nickel cathode plate;

[0039] S2, prepare 100mL of degreasing liquid according to 60g / L NaOH, 20g / L Na2CO3, 50g / L Na3PO4 and 10g / L Na2SiO3, prepare 100mL of activating liquid according to 50mL / L concentrated sulfuric acid and 10mL / L diluted hydrochloric acid with a mass fraction of 37%, immerse the pretreated stainless steel anode plate and pretreated pure nickel cathode plate prepared in step S1 in the degreasing liquid, subject them to ultrasonic treatment at a power of 400W for 10min, wash them with deionized water, transfer them to the activating liquid, soak them for 10s, wash them with deionized water and anhydrous ethanol in turn, and set them aside;

[0040] S3, prepare an electroplating solution according to 100 g / L nickel sulfate, 8 g / L sodium chloride, 30 g / L boric acid, 60 g / L sodium sulfate, and 0.1 g / L sodium dodecyl sulfate, adjust the pH to 5, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating process in this embodiment, and set the current density to 0.3 A / dm 2 , the temperature of the electroplating tank was set at 35°C, and after 4 minutes of electroplating treatment, the first deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0041] S4, prepare an electroplating solution according to 5 g / L of cobalt sulfate, 20 g / L of nickel sulfate, 200 g / L of chromium sulfate, 50 g / L of sodium citrate, 35 g / L of boric acid, 70 g / L of potassium chloride, 0.2 g / L of sodium dodecyl sulfate, and 0.4 g / L of dopant, adjust the pH of the electroplating solution to 2.5, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating treatment in the embodiment, and set the current density to 0.15 A / dm 2, the temperature of the electroplating tank was set at 35°C, and after 30 minutes of electroplating treatment, a second deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0042] S41, dissolving 5 g of n-butyl lithium in 100 mL of cyclohexane, accurately weighing 6.64 g of tetravinylcyclotetrasilazane and placing it in 22 mL of n-hexane, in a dry nitrogen atmosphere, mixing the n-butyl lithium-cyclohexane solution and the tetravinylcyclotetrasilazane-n-hexane solution evenly, adding 10 mL of tetramethylethylenediamine, stirring well at 150 rpm, reacting for 2 h, filtering, washing the retained solid with n-hexane, and vacuum drying to obtain a tetravinylcyclotetrasilazane lithium compound, which is stored in a vacuum or in an argon atmosphere;

[0043] S42, transfer the lithium tetravinylcyclotetrasilazane prepared in step S41 to 100 mL toluene-tetrahydrofuran-n-hexane (V 甲苯 :V 四氢呋喃 :V 正己烷 =3:3:4) mixed solvent, fully stirred under nitrogen atmosphere, added 4.85g TiCl4, raised the temperature to 80°C, continued stirring for 48h, filtered, removed the solvent in the filtrate, and obtained polytitanium silazane;

[0044] S43. Accurately weigh 3.5 g of polytitanium silazane and place it in a transparent flask. Add 35 mL of tetrahydrofuran, mix well, add 0.27 g of 2-mercaptoethanol, stir at 300 rpm, add 70 mg of benzoin dimethyl ether, and after the reactants are completely mixed and dissolved, keep stirring and place under ultraviolet light for reaction for 5 minutes. After the reaction is completed, remove excess tetrahydrofuran solvent in vacuo, place the reaction product in anhydrous methanol for precipitation, remove unreacted reactants, and vacuum dry at 50° C. for 12 hours to obtain a dopant;

[0045] The dopant prepared in this example was analyzed by infrared spectroscopy using a Fourier transform infrared spectrometer. The frequency range was 4000-500 cm -1 , Figure 1 The infrared spectrum of the dopant prepared in this embodiment is shown in the figure. The infrared characteristic peaks of each group of the dopant in this embodiment can be clearly analyzed, indicating that the dopant in this embodiment is successfully synthesized;

[0046] S5. Place the stainless steel treated in step S4 in a tube furnace, raise the temperature to 700° C. at 10° C. / min in an argon atmosphere, keep the temperature for 2 hours, and then naturally cool to room temperature in the furnace to obtain a corrosion-resistant metal surface composite coating material.

[0047] This embodiment also provides a corrosion-resistant metal surface composite coating material.

[0048] Example 2

[0049] This embodiment provides a method for preparing a corrosion-resistant metal surface composite coating material, which specifically includes the following steps:

[0050] S1. Take SS316L stainless steel as the anode, with a size of 10×30×1.5mm, take a pure nickel plate with a nickel content of 99.98% and a size of 40×40×3mm, pre-grind the SS316L stainless steel anode plate and the pure nickel cathode plate with a grinder, and then manually grind and polish with 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh SiC sandpaper in sequence, and use a DR300 high-precision roughness tester to test the surface roughness of the SS316L stainless steel anode plate and the pure nickel cathode plate, which are 2.4μm and 2.3μm, respectively. After grinding, use deionized water, acetone and anhydrous ethanol to clean the surfaces of the stainless steel anode plate and the pure nickel cathode plate in sequence to obtain a pretreated stainless steel anode plate and a pretreated pure nickel cathode plate;

[0051] S2, prepare 100mL of degreasing liquid according to 60g / L NaOH, 20g / L Na2CO3, 50g / L Na3PO4 and 10g / L Na2SiO3, prepare 100mL of activating liquid according to 50mL / L concentrated sulfuric acid and 10mL / L diluted hydrochloric acid with a mass fraction of 37%, immerse the pretreated stainless steel anode plate and pretreated pure nickel cathode plate prepared in step S1 in the degreasing liquid, subject them to ultrasonic treatment at a power of 400W for 10min, wash them with deionized water, transfer them to the activating liquid, soak them for 15s, wash them with deionized water and anhydrous ethanol in sequence, and set them aside;

[0052] S3, prepare an electroplating solution according to 100 g / L nickel sulfate, 8 g / L sodium chloride, 30 g / L boric acid, 60 g / L sodium sulfate, and 0.1 g / L sodium dodecyl sulfate, adjust the pH to 5, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating treatment in the embodiment, and set the current density to 0.3 A / dm 2 , the temperature of the electroplating tank was set at 35°C, and after 4 minutes of electroplating treatment, the first deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0053] S4, prepare an electroplating solution according to 4 g / L of cobalt sulfate, 20 g / L of nickel sulfate, 180 g / L of chromium sulfate, 40 g / L of sodium citrate, 35 g / L of boric acid, 80 g / L of potassium chloride, 0.2 g / L of sodium dodecyl sulfate, and 0.3 g / L of dopant, adjust the pH of the electroplating solution to 2.5, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating treatment in the embodiment, and set the current density to 0.15 A / dm2 , the temperature of the electroplating tank was set at 35°C, and after 30 minutes of electroplating treatment, a second deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0054] S41, dissolving 4 g of n-butyl lithium in 100 mL of cyclohexane, accurately weighing 4.80 g of tetravinylcyclotetrasilazane and placing it in 50 mL of n-hexane, in a dry nitrogen atmosphere, mixing the n-butyl lithium-cyclohexane solution and the tetravinylcyclotetrasilazane-n-hexane solution evenly, adding 5 mL of tetramethylethylenediamine, stirring well at 200 rpm, reacting for 1 h, filtering, washing the retained solid with n-hexane, and vacuum drying to obtain a tetravinylcyclotetrasilazane lithium compound, which is stored in a vacuum or in an argon atmosphere;

[0055] S42, transfer the tetravinylcyclotetrasilazane lithium prepared in step S41 to 70 mL toluene-tetrahydrofuran-n-hexane (V 甲苯 :V 四氢呋喃 :V 正己烷 =3:3:4) mixed solvent, fully stirred under nitrogen atmosphere, added 3.42g TiCl4, raised the temperature to 100°C, continued stirring for 36h, filtered, removed the solvent in the filtrate, and obtained polytitanium silazane;

[0056] S43. Accurately weigh 4 g of polytitanium silazane and place it in a transparent flask. Add 20 mL of tetrahydrofuran, mix well, add 0.31 g of 2-mercaptoethanol, stir at 300 rpm, add 0.12 g of benzoin dimethyl ether, and after the reactants are completely mixed and dissolved, keep stirring and place under ultraviolet light for reaction for 10 minutes. After the reaction is completed, remove excess tetrahydrofuran solvent in vacuo, place the reaction product in anhydrous methanol for precipitation, remove unreacted reactants, and vacuum dry at 50° C. for 12 hours to obtain a dopant;

[0057] S5. Place the stainless steel treated in step S4 in a tubular furnace, raise the temperature to 800° C. at 10° C. / min in an argon atmosphere, keep the temperature for 1 hour, and then naturally cool to room temperature in the furnace to obtain a corrosion-resistant metal surface composite coating material.

[0058] This embodiment also provides a corrosion-resistant metal surface composite coating material.

[0059] Example 3

[0060] This embodiment provides a method for preparing a corrosion-resistant metal surface composite coating material, which specifically includes the following steps:

[0061] S1. Take SS316L stainless steel as the anode, with a size of 10×30×1.5mm, take a pure nickel plate with a nickel content of 99.98% and a size of 40×40×3mm, pre-grind the SS316L stainless steel anode plate and the pure nickel cathode plate with a grinder, and then manually grind and polish with 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh SiC sandpaper in sequence, and use a DR300 high-precision roughness tester to test the surface roughness of the SS316L stainless steel anode plate and the pure nickel cathode plate, which are 2.5μm and 2.2μm, respectively. After grinding, use deionized water, acetone and anhydrous ethanol to clean the surfaces of the stainless steel anode plate and the pure nickel cathode plate in sequence to obtain a pretreated stainless steel anode plate and a pretreated pure nickel cathode plate;

[0062] S2, prepare 100mL of degreasing liquid according to 60g / L NaOH, 20g / L Na2CO3, 50g / L Na3PO4 and 10g / L Na2SiO3, prepare 100mL of activating liquid according to 50mL / L concentrated sulfuric acid and 10mL / L diluted hydrochloric acid with a mass fraction of 37%, immerse the pretreated stainless steel anode plate and pretreated pure nickel cathode plate prepared in step S1 in the degreasing liquid, subject them to ultrasonic treatment at a power of 400W for 10min, wash them with deionized water, transfer them to the activating liquid, soak them for 10s, wash them with deionized water and anhydrous ethanol in turn, and set them aside;

[0063] S3, prepare an electroplating solution according to 100 g / L nickel sulfate, 8 g / L sodium chloride, 30 g / L boric acid, 60 g / L sodium sulfate, and 0.1 g / L sodium dodecyl sulfate, adjust the pH to 5, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating treatment in the embodiment, and set the current density to 0.3 A / dm 2 , the temperature of the electroplating tank was set at 35°C, and after 4 minutes of electroplating treatment, the first deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0064] S4, prepare an electroplating solution according to 5 g / L of cobalt sulfate, 18 g / L of nickel sulfate, 150 g / L of chromium sulfate, 50 g / L of sodium citrate, 30 g / L of boric acid, 80 g / L of potassium chloride, 0.1 g / L of sodium dodecyl sulfate, and 0.2 g / L of dopant, adjust the pH of the electroplating solution to 3, use a pulsed AC electroplating power source as the pulse electroplating power source for the electroplating treatment in the embodiment, and set the current density to 0.15 A / dm 2 , the temperature of the electroplating tank was set at 35°C, and after 30 minutes of electroplating treatment, a second deposition layer was obtained on the stainless steel anode plate, which was washed three times with deionized water, acetone and anhydrous ethanol in sequence and then used for standby;

[0065] S41, dissolving 5 g of n-butyl lithium in 100 mL of cyclohexane, accurately weighing 6.00 g of tetravinylcyclotetrasilazane and placing it in 30 mL of n-hexane, in a dry nitrogen atmosphere, mixing the n-butyl lithium-cyclohexane solution and the tetravinylcyclotetrasilazane-n-hexane solution evenly, adding 8 mL of tetramethylethylenediamine, stirring well at 200 rpm, reacting for 2 h, filtering, washing the retained solid with n-hexane, and vacuum drying to obtain a tetravinylcyclotetrasilazane lithium compound, which is stored in a vacuum or in an argon atmosphere;

[0066] S42, transfer the tetravinylcyclotetrasilazane lithium prepared in step S41 to 108 mL toluene-tetrahydrofuran-n-hexane (V 甲苯 :V 四氢呋喃 :V 正己烷 =3:3:4) mixed solvent, fully stirred under nitrogen atmosphere, added 3.42 g TiCl4, raised the temperature to 90°C, continued stirring for 42 hours, filtered, removed the solvent in the filtrate, and obtained polytitanium silazane;

[0067] S43. Accurately weigh 3 g of polytitanium silazane and place it in a transparent flask. Add 30 mL of tetrahydrofuran, mix well, add 0.27 g of 2-mercaptoethanol, stir at 300 rpm, add 60 mg of benzoin dimethyl ether, and after the reactants are completely mixed and dissolved, keep stirring and place under ultraviolet light for reaction for 8 minutes. After the reaction is completed, remove excess tetrahydrofuran solvent in vacuo, place the reaction product in anhydrous methanol for precipitation, remove unreacted reactants, and vacuum dry at 50° C. for 12 hours to obtain a dopant;

[0068] S5. Place the stainless steel treated in step S4 in a tubular furnace, raise the temperature to 750° C. at 10° C. / min in an argon atmosphere, keep the temperature for 2 hours, and then naturally cool to room temperature in the furnace to obtain a corrosion-resistant metal surface composite coating material.

[0069] This embodiment also provides a corrosion-resistant metal surface composite coating material.

[0070] Comparative Example 1

[0071] This comparative example provides a metal surface composite coating material and a preparation method thereof, which differs from Example 1 only in that in step S4 of the preparation method, the electroplating plating solution does not include a dopant, and the remaining components, component contents and preparation method are the same as those of Example 1.

[0072] Comparative Example 2

[0073] This comparative example provides a metal surface composite coating material and a preparation method thereof, which is different from Example 1 only in that the preparation method does not include step S5, and the remaining components, component contents and preparation method are the same as those in Example 1.

[0074] Comparative Example 3

[0075] This comparative example provides a metal surface composite coating material and a preparation method thereof, which differs from Example 1 only in that, in step S4 of the preparation method, the preparation method of the electroplating plating solution does not include step S43, that is, the dopant is not activated by 2-mercaptoethanol, and the remaining components, component contents and preparation method are the same as those in Example 1.

[0076] Experimental Example 1

[0077] The microscopic morphology of the coating materials prepared in Example 1 and Comparative Example 1 was observed using a SU8220 field emission scanning electron microscope (SEM). Figure 2 The SEM images of the coating materials prepared in Experimental Example 1 and Comparative Example 1, image A is the coating material prepared in Example 1, and image B is the coating material prepared in Comparative Example 1. As shown in the figure, the surface of the coating material prepared in Example 1 of the present invention is smoother than that in Comparative Example 1, and the contact area between the coating and the corrosive medium can be reduced during the corrosion resistance process, thereby avoiding corrosion.

[0078] Experimental Example 2

[0079] In this experimental example, the corrosion resistance of the coating materials prepared in Examples 1-3 and Comparative Examples 1-3 was determined by potential dynamic polarization curves. The test was conducted on a CS310M electrochemical workstation with a three-electrode system. In a 3.5wt% NaCl solution, the coating materials in Example 1 and Comparative Examples 1-3 (including stainless steel plates) were used as working electrodes, platinum electrodes were used as counter electrodes, Ag / AgCl electrodes were used as reference electrodes, and bare steel was used as a blank. Dynamic polarization curves were drawn, and the anti-corrosion efficiency was calculated by the following formula:

[0080] ;

[0081] IcorrB is the corrosion current density of bare steel, in μA / cm 2 ; IcorrC is the corrosion current density of the coating materials prepared in Examples 1-3 and Comparative Examples 1-3, in μA / cm 2 ;

[0082] Figure 3The dynamic polarization curves of the coating materials and bare steel prepared in Example 1 and Comparative Examples 1-3 are shown. The dynamic potential polarization curve can provide the electrode potential formed by the change of polarization current density. The polarization current density is generally proportional to the corrosion rate. That is, the electrode with higher corrosion potential and lower corrosion current density has better corrosion resistance. The corrosion current density of Example 1 is 2.31×10 -7 A / cm -2 , the corrosion potential is 0.13V, the corrosion current density is significantly lower than that of comparative examples 1-3, while the corrosion potential is significantly higher than that of comparative examples 1-3, and the anti-corrosion performance is relatively high; Figure 4 The anti-corrosion efficiency result diagram of Examples 1-3 and Comparative Examples 1-3 is shown in the figure. In Comparative Example 1, the second deposition layer of the coating material does not include a dopant. After adding the dopant, the formed metal coating has a highly dense structure. When they are dispersed in the metal coating, they will form a physical barrier to hinder the penetration of corrosive media (such as water, oxygen, chloride ions, etc.). This shielding effect can reduce the direct contact between the corrosive media and the metal substrate, thereby reducing the corrosion rate; the coating in Comparative Example 2 has not been subjected to high-temperature treatment. After high-temperature treatment, the coating The degree of ceramicization is better, and the formed metal deposition layer is denser, which can hinder the penetration of corrosive media; the dopant described in Comparative Example 3 has not been activated by 2-mercaptoethanol, and 2-mercaptoethanol can be connected to polytitanium silazane through a mercapto double bond click reaction. Polytitanium silazane is highly hydrophobic and unevenly dispersed in the plating solution. After functional modification, the dispersibility of polytitanium silazane in the plating solution can be significantly improved, and the hydroxyl group can promote the nucleation and growth of the metal, which is beneficial to the flatness of the coating and reduces the contact area with the corrosive medium, thereby improving the corrosion resistance.

[0083] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0084] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant metal surface composite coating material, characterized in that: The specific steps include: S1. Pre-grind the stainless steel and nickel plate with a grinder, and then grind the stainless steel surface with 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh sandpaper in sequence, polish until the sample roughness is 2-2.5 μm, wash with deionized water, acetone, and anhydrous ethanol in sequence to obtain pre-treated stainless steel for electrodeposition treatment of cathode, and obtain pre-treated nickel plate for electrodeposition treatment of anode for standby use; S2, immersing the pretreated stainless steel and pretreated nickel plate in the degreasing solution, ultrasonically treating them at 400W for 15 minutes, washing them with deionized water, placing them in the activation solution, soaking them for 10-15 seconds, washing them with deionized water and anhydrous ethanol, and setting them aside; S3. Prepare the electroplating solution according to the following mass concentrations: nickel sulfate 100 g / L, sodium chloride 8 g / L, boric acid 30 g / L, sodium sulfate 60 g / L, sodium dodecyl sulfate 0.1 g / L, adjust the pH of the electroplating solution to 5, adjust the electroplating treatment parameters, and the current density is 0.3 A / dm 2 , the electrodeposition temperature is 35°C, the electrodeposition treatment time is 4 minutes, and the first deposition layer is obtained; S4. Prepare the electroplating solution according to the following mass concentrations: 4-5 g / L cobalt sulfate, 18-20 g / L nickel sulfate, 150-200 g / L chromium sulfate, 40-50 g / L sodium citrate, 30-35 g / L boric acid, 70-80 g / L potassium chloride, 0.1-0.2 g / L sodium dodecyl sulfate, 0.2-0.4 g / L dopant, adjust the pH of the electroplating solution to 2.5-3, adjust the electroplating parameters, and the current density is 0.15 A / dm 2 , the electrodeposition temperature is 35°C, the electrodeposition time is 30 min, and the second deposition layer is obtained; S41, dissolving n-butyl lithium in cyclohexane, adding tetravinylcyclotetrasilazane solution under a dry nitrogen atmosphere, mixing evenly, adding tetramethylethylenediamine, stirring well at 150-200 rpm, reacting for 1-2 hours, filtering, washing the retained solid with n-hexane, and vacuum drying to obtain a tetravinylcyclotetrasilazane lithium compound, which was stored under an argon atmosphere; S42, transferring the tetravinylcyclotetrasilazane lithium prepared in step S41 into a toluene-tetrahydrofuran-n-hexane mixed solvent, fully stirring under a nitrogen atmosphere, adding titanium tetrachloride, raising the temperature to 80-100° C., stirring and reacting for 36-48 hours, filtering, removing the solvent in the filtrate, and obtaining polytitanium silazane; S43, dissolving the polytitanium silazane prepared in step S42 in tetrahydrofuran, adding 2-mercaptoethanol, mixing evenly, adding benzoin dimethyl ether, stirring at 300 rpm, reacting under ultraviolet light for 5-10 minutes, removing the tetrahydrofuran solvent after the reaction is completed, precipitating with anhydrous methanol, removing unreacted reactants, and vacuum drying to constant weight to obtain a dopant; S5. Place the stainless steel treated in step S4 in a tubular furnace, raise the temperature to 700-800° C. at 10° C. / min in an argon atmosphere, keep the temperature for 1-2 hours, and then naturally cool to room temperature in the furnace to obtain a corrosion-resistant metal surface composite coating material.

2. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 1, characterized in that: In step S2, the degreasing liquid specifically includes components with the following concentrations: NaOH 60 g / L, Na2CO3 20 g / L, Na3PO4 50 g / L, Na2SiO3 10 g / L; the activation solution specifically includes components with the following concentrations: concentrated sulfuric acid 50 mL / L, dilute hydrochloric acid with a mass fraction of 37% 10 mL / L.

3. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 2, characterized in that: In step S41, the mass fraction of n-butyl lithium in cyclohexane is 40-50 g / L; the amount of tetramethylethylenediamine added is 5-10% of the volume of cyclohexane; and the molar ratio between n-butyl lithium and tetravinylcyclotetrasilazane is 4-4.5:

1.

4. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 3, characterized in that: In step S41, the tetravinylcyclotetrasilazane solution is tetravinylcyclotetrasilazane dissolved in n-hexane, and the mass concentration of the tetravinylcyclotetrasilazane solution is 0.1-0.3 g / mL.

5. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 4, characterized in that: In step S42, the mass concentration of the tetravinylcyclotetrasilazane lithium compound in the mixed solvent is 50-60 g / L.

6. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 5, characterized in that: In step S42, the molar ratio between the lithium tetravinylcyclotetrasilazane and titanium tetrachloride is 1:1.2-1.

5.

7. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 6, characterized in that: In step S43, the mass concentration of the polytitanium silazane in tetrahydrofuran is 0.1-0.2 g / mL.

8. The method for preparing a corrosion-resistant metal surface composite coating material according to claim 7, characterized in that: In step S43, the mass ratio of the 2-mercaptoethanol to the polytitanium silazane is 1:11-13; the added mass of the benzoin dimethyl ether is 2%-3% of the mass of the polytitanium silazane.

9. A corrosion-resistant metal surface composite coating material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of corrosion-resistant structure of petroleum stainless steel pipeline

    CN110468437A

  • Polytitanium silazane corrosion-resistant coating and preparation method thereof

    CN115558420A